2018
DOI: 10.1371/journal.pone.0200517
|View full text |Cite
|
Sign up to set email alerts
|

The effects of beetroot juice supplementation on exercise economy, rating of perceived exertion and running mechanics in elite distance runners: A double-blinded, randomized study

Abstract: PurposeNitrate-rich beetroot juice supplementation has been extensively used to increase exercise economy in different populations. However, its use in elite distance runners, and its potential effects on biomechanical aspects of running have not been properly investigated. This study aims to analyze the potential effects of 15 days of beetroot juice supplementation on physiological, psychological and biomechanical variables in elite runners.MethodsTwelve elite middle and long-distance runners (age = 26.3 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
2
18
2
Order By: Relevance
“…The methodological quality of the articles, evaluated using McMaster's Critical Review Form [21], ranged between 13 and 15 points, representing a minimum methodological quality of 86.6% and a maximum of 100%. Of the 27 studies, 3 achieved 13 items, representing 11.11% of the total number of studies, 3 achieved 14 items, representing the same percentage of 11.11%, and the rest of the studies (21) achieved 15 items, representing 77.78% of the total number of studies.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%
“…The methodological quality of the articles, evaluated using McMaster's Critical Review Form [21], ranged between 13 and 15 points, representing a minimum methodological quality of 86.6% and a maximum of 100%. Of the 27 studies, 3 achieved 13 items, representing 11.11% of the total number of studies, 3 achieved 14 items, representing the same percentage of 11.11%, and the rest of the studies (21) achieved 15 items, representing 77.78% of the total number of studies.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%
“…Dietary supplements, such as creatine, caffeine and sodium bicarbonate, have a strong historical evidence basis to support ergogenic effects in certain exercise settings [ 34 ]. More recently, inorganic nitrate (NO 3 − ) ingestion, often administered as concentrated NO 3 − -rich beetroot juice (BR), has been reported to confer ergogenic effects in various exercise modalities [ 35 ], including running [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], rowing [ 48 , 49 ], kayaking [ 50 ], knee extensions [ 37 , 51 ] and cycling [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Although an ergogenic effect of NO 3 − supplementation appears less likely in endurance-trained individuals, i.e., [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], recent systematic reviews support its efficacy as an ergogenic aid during continuous endurance-type exercise [ 75 , 76 , 77 ] and high-intensity intermittent-type exercise [ 7...…”
Section: Introductionmentioning
confidence: 99%
“…Also, time to exhaustion has been shown to significantly improve after 15 days of BRJ supplementation. However, VO 2max wasn't improved after the trial (Balsalobre-Fern andez et al 2018). Another benefit from consuming BRJ for a short period in well-trained rowers was that the maximal rowing-ergometer repetitions improved (Bond, Morton, and Braakhuis 2012).…”
Section: Well-trained Menmentioning
confidence: 97%
“…Indeed, Hoon et al (2015) found that four-day BRJ supplementation in healthy individuals decreased muscular fatigue in conditions of reduced blood flow during exhaustive exercise (Hoon et al 2015), and Husmann et al (2019) found reduced perceived effort and muscle pain after five-day BRJ ingestion (Husmann et al 2019). Additionally, several studies have found that BRJ improves exercise tolerance or rate of perceived exhaustion in normoxia (Aucouturier et al 2015;Bailey et al 2015;Balsalobre-Fern andez et al 2018;Breese et al 2013;Wylie, Kelly, Fulford, et al 2013) as well as hypoxia (Kelly et al 2014;Vanhatalo et al 2011). Other studies, however, have failed to show such an effect on oxidative stress (Carriker et al 2018), rate of fatigue or perceived exertion (de Castro, de Assis Manoel, et al 2019;Lee et al 2019).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 99%